Efektifitas Layanan KonselingPerorangan Meningkatkan Kemandirian Siswa Dalam Menyelesaikan Masalah Belajar - Hanum, Muthia; Prayitno, Prayitno; Nirwana, Herman (Universitas Negeri Padang, 2015)
This study was aimed to score the difference of students` independence in solving learning problems before and after following individual counseling service. It was a quantitative research, an experimental research with the design of pretest and postest. It involved 20 students of SMP Negeri 3 Payakumbuh, who had learning problems and served by their school counselors by individual counseling service. The data of pretest scores (81.00) and postest scores (149.00). Difference was significant. This study concluded that the individual counseling service gives a significant effect to the improvement of students` independency in solving learning problems.